Influence of broiler pre-slaughter fasting on weight loss and contamination by Salmonella spp. in the crop and antibacterial efficacy of the carcass bath with a blend of organic acids and essential oil (Research, Society and Development, 2020)
In the search of techniques that can helps in the reduction of microorganisms that can be present during slaughter, research is being done with the use of organic acids and essential oils as a sanitizer for the carcasses. The objective of the present study was to evaluate the influence of pre-slaughter fasting on broilers on weight loss and contamination by Salmonella spp. in the crop and the efficacy of the carcasses bath with a blend of organic acids and essential oil in the reduction of microorganisms indicate contamination. Three lots of broiler chickens from an integration were evaluated, and only two lots were evaluated for weight loss after the fasting period. Samples of 40 broilers were taken from each lot. The product used was diluted in concentrations of 4, 8 and 12%. The analysis of the presence of contamination indicator microorganisms was made: (1) before the final toilet; (2) after the final toilet and (3): after the chiller. It was found that weight loss varied between the two lots evaluated. The aerobic mesophiles count was reduced in the concentration of 12% of the commercial blend after the final toilet. The cooling ( chiller) of the carcass was efficient in reducing aerobic mesophiles count in 66.6% (2/3) of the lots. Coliforms at 45°C were presented in 66.6% (2/3) of the lots and the count of psychrotrophic microorganisms varied between the lots evaluated. Further studies are needed to evaluate the effect of the blend directly in the final toilet shower, in order to evaluate its effectiveness on a large scale of production.